2011
DOI: 10.1590/s0102-695x2011005000039
|View full text |Cite
|
Sign up to set email alerts
|

Maytenus salicifolia Reissek, Celastraceae: triterpenes isolated from stems and antioxidant property of extracts from aerial parts

Abstract: Six pentacyclic triterpenes were isolated from hexane extract of stems of Maytenus salicifolia Reissek, Celastraceae: 30-hydroxyfriedelan-3-one (1), 3,16-dioxofriedelane (2), friedeline (3), lupeol (4), betuline (5) and lup-20(29)-en-3,30-diol (6). The structure each one was established on the basis of detailed 1 H and 13 C NMR spectral investigation and by comparison with the respective literature values. For compound 1, the complete 2D NMR (HMBC, HMQC and NOESY) spectral data were herein reported for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
1
10
0
3
Order By: Relevance
“…Antonisamy et al presented a study with a pentacyclic triterpene isolated from Azimate tracantha (Salvadoraceae) that demonstrated an anti-inflammatory, analgesic, and antipyretic effect in mouse and rat models [3]. Montanha et al demonstrated this effect from the Loranthus regularis (Loranthaceae) extract and identified the phenolic constituents in this material [15], while Magalhães et al and Souza et al described antioxidant properties from Maytenus salicifolia (Celastraceae) and Stachytarpheta cayennensis (Verbenaceae) extracts [13,14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antonisamy et al presented a study with a pentacyclic triterpene isolated from Azimate tracantha (Salvadoraceae) that demonstrated an anti-inflammatory, analgesic, and antipyretic effect in mouse and rat models [3]. Montanha et al demonstrated this effect from the Loranthus regularis (Loranthaceae) extract and identified the phenolic constituents in this material [15], while Magalhães et al and Souza et al described antioxidant properties from Maytenus salicifolia (Celastraceae) and Stachytarpheta cayennensis (Verbenaceae) extracts [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, another compound was obtained from fractions 86-89 after chromatographic separation; its NMR data were almost identical to those of euphol, although there were small differences resembling a stereoisomer of euphol. The main differences in 13 C NMR data were observed for the carbons C-12, C-14, C-16, C-17, C-20, and C-22 at 30.9, 51.0, 28.2, 50.1, 36.4, and 36.4, respectively, which were in accordance with those described in the literature for lanosterol [17,18]. Friedelin has been found in other species of Euphorbiaceae such as Mallotus barbatus [35] and Drypetes gossweileri [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that this family comprises a total of 1350 species belonging to 96 different genera . Many Celastraceae species present pharmacological activities such as antitumor, anti‐inflammatory, antimicrobial, antioxidant, antiviral, analgesic, and acetylcholinesterase inhibitor …”
Section: Introductionmentioning
confidence: 99%
“…Many of the chemical components isolated from its species have pharmacological properties (Din et al 2013, Duarte et al 2013, Moo-Puc et al 2014 (Silva et al 2009, Rodrigues et al 2012, M. aquifolium Mart., (Gonzalez et al 2001), M. salicifolia Reissek, (Magalhães et al 2011) and M. truncata Reissek, (Silva et al 2005a) are used in folk medicine to treat the same stomach illness, and have the same popular name "espinheira-santa" (Niero et al 2011). For these reasons it is necessary a careful quality control of raw material in the manufacture of drugs using Maytenus species and is required define anatomical key characters for the unambiguous species identification (Jacomassi & Machado 2004, Duarte & Debur 2005, Joffily & Vieira 2005, Nakamura et al 2013.…”
mentioning
confidence: 99%